The Effect Of Product And Service Quality On Customer Loyalty Mediated By Customer Satisfaction In Micro Small Business Multi Cipta Semarang - Choirul Ichsan; Bambang Guritno; Hendrajaya Hendrajaya (International Conference On Digital Advanced Tourism Management And Technology, 2023)
Research located at Toko Multi Cipta Semarang has objectives that are divided into two types, namely the general purpose is to analyze and explain the effect of products and service quality on customer loyalty mediated by customer satisfaction in Micro Small Enterprises Multi Cipta Semarang, and for its special purpose is to analyze and explain: 1) the effect of products on customer satisfaction, 2) the effect of service quality on customer satisfaction, 3) the effect of the product on customer loyalty, 4) the effect of service quality on customer loyalty. 5) the effect of customer satisfaction on customer loyalty, 6) the effect of products on customer loyalty mediated by customer satisfaction, and 7) the effect of service quality on customer loyalty mediated by customer satisfaction . The sample used in this study was 138 people, then given the opportunity to answer questionnaires that would be processed using the SPSS 25.0 application to produce numbers which were then tested for feasibility using validity tests and reliability tests. For data analysis techniques used are multiple regression analysis, model testing and hypothesis testing .The results of the study concluded that: the general conclusion states that customer satisfaction does not mediate the effect of product and service quality on customer loyalty, while the specific conclusion states that: 1) product affects customer satisfaction, 2) service quality affects customer satisfaction, 3) product affects customer loyalty, 4) service quality affects customer loyalty, 5) customer satisfaction affects customer loyalty. Customer loyalty, 6) customer satisfaction does not mediate the effect of the product on customer loyalty, and 7) customer satisfaction does not mediate the effect of service quality on customer loyalty.